2015
DOI: 10.1055/s-0035-1547361
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Monitoring of the Lateral Spread Response Resulting from Serial Decompression for Hemifacial Spasm Caused by a Fusiform Aneurysm

Abstract: Fusiform aneurysm as a cause of hemifacial spasm (HFS) is an extremely rare condition. A 69-year-old man developed paroxysmal spasm of his left side facial muscles over a period of 5 years. Radiologic images demonstrated a left vertebral artery (VA) fusiform aneurysm compressing the root entry zone of the left facial nerve. The patient underwent serial surgical procedures for the treatment of HFS under intraoperative electromyography monitoring. Lateral spread response (LSR) did not disappear despite 5 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, trapping is indicated only when the affected VA is smaller than or equal to the contralateral VA in size and the origin of the PICA is located distal to the affected segment of the DVAA, owing to the ischemic risk following trapping. Lee et al 21 reported that the resolution of HFS associated with DVAA was achieved by simple decompression of the DVAA from the REZ of the facial nerve via retrosigmoid craniotomy, because the DVAA was not likely to be an active lesion on angiographic and intraoperative examination, and there was ambiguity with respect to the dominance of the origin of the VA and PICA, which is critical in formulating the treatment strategy for DVAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, trapping is indicated only when the affected VA is smaller than or equal to the contralateral VA in size and the origin of the PICA is located distal to the affected segment of the DVAA, owing to the ischemic risk following trapping. Lee et al 21 reported that the resolution of HFS associated with DVAA was achieved by simple decompression of the DVAA from the REZ of the facial nerve via retrosigmoid craniotomy, because the DVAA was not likely to be an active lesion on angiographic and intraoperative examination, and there was ambiguity with respect to the dominance of the origin of the VA and PICA, which is critical in formulating the treatment strategy for DVAA.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the HFS results from NVC, there are secondary causative etiologies, such as a tumor in the posterior fossa, posterior circulation aneurysms, and vascular malformations, accounting for 0.3 to 2.5% of cases. 1 13 14 15 16 17 Among the secondary etiologies, the incidence of posterior circulation aneurysms as a major cause of HFS is much rarer with a rate of occurrence of 0.08 to 0.44%, 18 which has been reported sporadically in the form of case reports 18 19 20 21 22 23 24 25 26 27 or a few cases within large case series. 28 29 VA dissection, which is the most probable etiology of fusiform aneurysms, has been reported scarcely.…”
Section: Discussionmentioning
confidence: 99%